쌀 식빵의 소비자 지불의사가치 분석 - 이상호; Lee Sang-Ho (농업생명과학연구, 2018)
이 논문에서는 쌀 식빵에 대한 소비자의 지불의향 및 가치를 분석하였다. 주요 분석결과를 정리하면 다음과 같다. 첫째, 건강에 대한 소비자의 관심도를 조사한 결과 응답자의 62.0%인 188명이 건강에 대 해 고관심 군으로 분석되었다. 이는 식품소비에 있어 가격뿐만 아니라 건강 등 식품의 속성요인에 소비 자의 관심이 높다는 것을 의미한다. 둘째, 쌀 식빵에 대한 응답자의 지불의사분포를 살펴보면 제시금액 이 높을수록 구매의향이 낮은 것으로 나타났다. 즉 쌀 식빵에 대한 소비자지불의향은 일반적 수요법칙 을 따르는 것으로 분석되었다. 셋째, 로짓모형을 통해 쌀 식빵에 대한 지불의향을 분석한 결과, 질병이 있을수록, 가족수가 많을수록 쌀로 만든 식빵에 대해 구매 확률이 높은 것으로 나타났다. 한편, 가격(제 시금액)이 높을수록 쌀로 만든 식빵에 대한 구매의향은 낮아짐을 알 수 있다. 넷째, 쌀로 만든 식빵에 대한 평균 지불의사금액은 500g당 4,979.7원으로 분석되었다. 즉 이는 밀가루 식빵 대비 약 2.5배의 가격 프리미엄이 있다는 것을 의미한다. The paper aims to analyze the willingness to pay for the rice bread. The main results of the key analysis is as follows. First, a survey of consumers’interest in health care has revealed that 62 percent of the respondents concerned about health care. This means consumer interest is high in terms of food quality, not just in terms of price factors. Second, according to the distribution of respondents’willingness to pay for the rice bread, the higher the offer, the less likely the purchase will be. It is analyzed that consumers ' willingness to pay for the rice bread is subject to the rule of general demand. Third, we analyzed the intention of payment of the rice bread through the Logit model. The higher the number of diseases, the higher the number of households, the more likely it is to buy a lot of bread. On the other hand, the higher the price, the lower the willingness to buy rice for the bread made of rice. Fourth, the average willingness to pay for bread made with rice was 4,979.7 won per 500 grams. That means there are approximately 2.5 times the price premium for the flour bread.